Evaluation of a porcine coproduct (pro-blend 75®) from slaughter plants as a protein source for starter pig diets - D J Lee; B R Dunsford; K L Herkelman; J D Hahn; Joe D Hancock; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1998)
Pellet durability index was greatest when animal protein products (dried whey, fish meal, spray-dried blood cells, and a porcine coproduct) were used in place of soybean meal. However, no differences occurred in ADG, ADFI, or F/G among segregated early-weaned piglets (10.1 lb) fed the various protein sources.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Animal Protein; Soybean meal; Nursery pigs